Extremely Low Frequency Electromagnetic Field Radiation (50 Hz, 200 µT & 300 µT) to Increase Edamame Productivity and Safety Risks to Health - Sudarti Sudarti; Elok Permatasari; Sumardi Sumardi; Wahyu Muldayani; Ega Bonansyah Utoyo; Winaning Nur Prihatin (Postgraduate, University of Mataram, 2023)
More and more research results report that exposure to Extremely Low Frequency (ELF) magnetic fields at low intensity can increase cell proliferation. The ELF magnetic field interacts directly with cell membranes, capable of increasing intracellular calcium and under certain conditions affecting cell proliferation. This study wanted to prove the potential of ELF magnetic field radiation with intensity of 200 µT and 300 µT on edamame productivity. The research design used a completely randomized design. The research sample was 250 edamame soybeans of the Ryokkoh-75 variety which were divided into 5 groups. Samples were soaked in warm water for 3 hours and then cured for about 12 hours and exposed to ELF magnetic fields of intensity of 200 µT and 300 µT with variations in exposure time of 60 minutes and 120 minutes. Then it is seeded and planted in the field. Observation of the number of edamame pods and the number of pods was carried out when they were already fruiting, namely day 29 to day 43. The results of the study proved that the number of pods and the number of edamame pods in the group exposed to the 200 µT and 300 µT ELF magnetic fields was higher than the control. It appears that the highest number of fruits and pods occurred in the sample group exposed to the ELF magnetic field intensity of 300 µT. The conclusion is that exposure to the ELF magnetic field intensity of 300 µT has the potential to increase edamame productivity